Optimality and duality for multiobjective fractional programming involving non-smooth generalized -univex functions - Liu, Jen-Chwan; Liu, Chun-Yu (International journal of mathematics and mathematical sciences, 2013)
We establish properly efficient necessary and sufficient optimality conditions for multiobjective fractional programming involving nonsmooth generalized (F, b, [phi], [rho], [theta])-univex functions. Utilizing] the necessary optimality conditions, we formulate the parametric dual model and establish some duality results in the framework of generalized (F, b, [phi], [rho], [theta])-univex functions.